Fecal indicators and antibiotic resistance genes exhibit diurnal trends in the Chattahoochee River: Implications for water quality monitoring - Nguyen, Karena. H.; Smith, Shanon; Roundtree, Alexis; Feistel, Dorian J.; Kirby, Amy E.; Levy, Karen; Mattioli, Mia Catharine (Frontiers in Microbiology, 2022)
Water bodies that serve as sources of drinking or recreation are routinely monitored for fecal indicator bacteria (FIB) by state and local agencies. Exceedances of monitoring thresholds set by those agencies signal likely elevated human health risk from exposure, but FIB give little information about the potential source of contamination. To improve our understanding of how within-day variation could impact monitoring data interpretation, we conducted a study at two sites along the Chattahoochee River that varied in their recreational and commercial usage, collecting samples every thirty minutes over one 24-hour period. We assayed for three types of microbial indicators: FIB (total coliforms and Escherichia coli); human fecal-associated microbial source tracking (MST) markers (crAssphage and HF183/BacR287); and a suite of environmentally common and/or clinically relevant antibiotic resistance genes (ARGs; intI1, blaCTX-M, blaCMY, MCR, KPC, VIM, NDM). Mean levels of FIB and clinically relevant ARGs (blaCMY and KPC) were similar across sites, while MST markers and commonly occurring ARGs (intI1) occurred at higher mean levels at the recreational site. The human-associated MST markers positively correlated with ARGs at both sites, but no consistent associations were detected between FIB and MST markers or FIB and ARGs. For all microbial indicators, generalized additive mixed models were used to examine diurnal variability and whether this variability was associated with environmental factors (water temperature, turbidity, pH, and sunlight). We found that FIB peaked during morning and early afternoon hours and were not associated with environmental factors. MST markers and intI1 exhibited diurnal variability; water temperature, pH, and turbidity were significant predictors of diurnal variability. One exception occurred at the commercial site, where HF183/BacR287 showed no diurnal variability. For blaCMY and KPC, diurnal variability was present but was not correlated with environmental factors. These results suggest that differences in land use (recreational or commercial) may impact overall levels of contamination. Monitoring agencies should consider matching sample collection times with peak levels of target microbial indicators, which would be in the morning or early afternoon for most indicators. Measuring multiple microbial indicators can lead to clearer interpretations of human health risk associated with exposure to contaminated water.